Breast cancer brain metastasis: Current evidence and future directions. (13th July 2022) - Sun, Hongna; Xu, Junnan; Dai, Shuang; Ma, Yiwen; Sun, Tao
Abstract: Breast cancer is the most common cancer in women and the second leading cause of cancer‐related deaths after lung cancer. Metastasis of the central nervous system is a terrible event for breast cancer patients, affecting their survival and quality of life. Compared with hormone receptor‐positive/human epidermal growth factor receptor 2‐negative breast cancer patients, brain metastases are more likely to affect patients with triple‐negative breast cancer and human epidermal growth factor receptor 2‐positive breast cancer. The treatment of breast cancer has improved greatly in the last two decades. However, brain metastases from breast cancer remain the leading cause of morbidity and mortality. Patients with breast cancer brain metastasis have been in an inferior position due to the lack of clinical research in this field, and they are often explicitly excluded from almost all clinical trials. The occurrence and progression of brain metastases will result in severe cognitive impairment and adverse physical consequences, so we must have a good understanding of the molecular mechanisms of breast cancer brain metastasis. In this article, we have retrieved the latest literature of molecules and pathways associated with breast cancer brain metastasis, summarized common therapy strategies, and discussed the prospects and clinical implications of targeting the molecules involved. Abstract : A portion of cells at the primary site acquired invasive properties by EMT. Invasive cancer cells intravasate into the bloodstream, survive, and arrest the circulatory system. Then these cells extravasate through transendothelial migration, colonize, and form metastatic brain lesions. BBB plays a critical role in ensuring normal brain function. However, as the development of primary or metastatic tumors in the brain, BBB becomes disrupted, and is altered to BTB. At last, new, and aberrant vessels grow during tumor progression.